Dari Kebiasaan ke Karakter: Pembiasaan Gemar Membaca pada Anak TK A - jesica - Mulyadi; Astri - Anita; Sitty Fadhilla Fitrianty Lahay (Universitas Negeri Gorontalo, 2026)
The Indonesian Children's Habits Programme (KAIH) is one of the government's efforts to shape positive character and habits in early childhood, including building an interest in reading. This community service activity aims to increase knowledge and interest in reading among kindergarten students through educational videos. The activity was carried out at Aisyiyah Bustanul Athfal Bolihuangga Kindergarten in Gorontalo Regency on 14 October 2025 with 17 students participating. The stages of the activity included preparation, screening of educational videos, interactive discussions, and evaluation. The evaluation results showed an increase in knowledge related to reading skills from 29.41% to 70.59%, as well as an increase in knowledge about the benefits of reading from 41.18% to 88.24%. These findings indicate that the use of educational videos is effective in increasing students' understanding and interest in reading activities. Thus, audio-visual media-based learning strategies can be a relevant alternative for fostering a culture of reading from an early age. Keywords: Indonesian Children's Habits Programme (KAIH), early childhood, educational videos, interest in reading, early literacy, kindergarten.